ANALISIS KORELASI ANTARA LINGKUNGAN KERJA DENGAN MOTIVASI KERJA KARYAWAN ( Studi Pada Component Management Section, Mining Support Division PT. Kaltim Prima Coal) - Arakian, Krisanto (PREDIKSI, 2016)
This study aims to determine the work environment, motivation and the correlation between the work environment with employee motivation Component Management Section, Mining Support Division PT. Kaltim Prima Coal. This study uses a quantitative descriptive approach. Results showed results showed that there was significant relation of the work environment with work motivation, because the value of empirical r r greater than the theoretical value or 0.390> 0.189. The results also show that there is a significant relationship and influence between work environment with work motivation, because the t-test results that do produce value 4.320. These results were compared with the prices of critical tables t-test for n - 2 (106-2 = 104) amounted to 1,983, then t-theoretical larger than t-empirical (4.320 Ëƒ 1,983). Thus the hypothesis in this study can be answered and substantiated.Â